Expressed sequence tags (ESTs) from young leaves of Metroxylon sagu - Ching, Ching Wee; Hairul, Azman Roslan (Springer, 2012)
Sago palm, or Metroxylon sagu, is a hardy and versatile plant that is able to tolerate many stresses, biotic and abiotic, during its growth. It is one of the plants that are able to grow in waterlogged area where others could not. Apart from that sago palm is also a source of starch, contributes economically to the people and an important export for the state of Sarawak. Despite the importance of sago palm especially in the production of starch and its ability to withstand stresses, so far, not many molecular studies have been reported on sago palm. To study the characters in sago palm, transcriptome analysis was conducted where it would give a better understanding of the plant development through gene expression. Here, we report the construction of a cDNA library and preliminary expressed sequence tags analysis from the young leaves of sago palm. A total of 434 clones were sequenced with inserts ranging from 1,000 to 3,000 bps with primary and amplified titers of 8 9 105 and 1.0 9 109 pfu/ml, respectively. Clustering of these sequences resulted in a set of 372 tentative unigenes comprising 340 singletons and 32 contigs. The database was also annotated with BLAST2GO which showed that majority of the transcripts were involved in primary metabolism and stress tolerance.